SHIFTING SOCIAL CONTROL AND THE DIRECTION OF LAW ENFORCEMENT IN THE VINA CIREBON CASE THROUGH THE CORRECTIVE FUNCTION OF SOCIAL MEDIA TOWARDS LAW IN ACTION - Achmad Benyamin Daniel; Lia Christine; Catharina Dewi Wulansari (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
the paradigm of social control from formal institutional mechanisms to informal, social media–based control in the digital era. The research is grounded in the prolonged stagnation of case handling, which exposed a significant gap between Law in the Books and Law in Action, later corrected through massive digital public pressure following the case's viral resurgence. The urgency of this study lies in understanding how social media facilitates the transformation of social control, performs a corrective function toward law enforcement practices, and reshapes public perceptions of the legitimacy and authority of the formal judicial system. This research employs a normative juridical method with a sociology of law perspective, using statutory, case, and conceptual approaches, supported by secondary data analyzed through qualitative descriptive-analytical techniques. The findings demonstrate that social media has emerged as a powerful instrument of informal social control capable of compelling law enforcement institutions to become more responsive and transparent, while simultaneously revealing a growing dependence of law enforcement on virality. Conversely, intense digital public pressure also generates risks, including reactive law enforcement, procedural haste, erosion of due process, and threats to the presumption of innocence. This study concludes that law enforcement in the digital age requires a careful balance between critical public oversight and consistent adherence to formal legal procedures in order to safeguard the rule of law and maintain the legitimacy of the justice system.